Carboxymethyl Hyaluronan-Stabilized Nanoparticles for Anticancer Drug Delivery - Jessica L. Woodman; Min Sung Suh; Jianxing Zhang; Yuvabharath Kondaveeti; Diane J. Burgess; Bruce A. White; Glenn D. Prestwich; Liisa T. Kuhn (International Journal of Cell Biology)
Carboxymethyl hyaluronic acid (CMHA) is a semisynthetic derivative of HA that is recognized by HA binding proteins but contains an additional carboxylic acid on some of the 6-hydroxyl groups of the N-acetyl glucosamine sugar units. These studies tested the ability of CMHA to stabilize the formation of calcium phosphate nanoparticles and evaluated their potential to target therapy resistant, CD44+/CD24−/low human breast cancer cells (BT-474EMT). CMHA stabilized particles (nCaPCMHA) were loaded with the chemotherapy drug cis-diamminedichloroplatinum(II) (CDDP) to form nCaPCMHACDDP. nCaPCMHACDDP was determined to be poorly crystalline hydroxyapatite, 200 nm in diameter with a −43 mV zeta potential. nCaPCMHACDDP exhibited a two-day burst release of CDDP that tapered resulting in 86% release by 7 days. Surface plasmon resonance showed that nCaPCMHACDDP binds to CD44, but less effectively than CMHA or hyaluronan. nCaPCMHA-AF488 was taken up by CD44+/CD24− BT-474EMT breast cancer cells within 18 hours. nCaPCMHACDDP was as cytotoxic as free CDDP against the BT-474EMT cells. Subcutaneous BT-474EMT tumors were more reproducibly inhibited by a near tumor dose of 2.8 mg/kg CDDP than a 7 mg/kg dose nCaPCMHACDDP. This was likely due to a lack of distribution of nCaPCMHACDDP throughout the dense tumor tissue that limited drug diffusion.